An Assessment of Cost of Access to Health Services of Severely Disabled People in Chitwan - Poudel, Chudamani; Baral, Ramesh (Economic Journal of Development Issues, 2018)
There are many barriers that keep people with disabilities from fully engaging in health care services. This study assessed the direct medical, direct non-medical and indirect cost as well as potential barriers and obstacles that people with spinal cord injury and intellectual disabilities faced in accessing health care services. This study conducted in Chitwan district of Nepal used both quantitative and qualitative information. For quantitative study, structured interview were conducted to assess the cost involved in health care services with 60 persons divided into Physical (spinal cord injury) and intellectual disability. In-depth interviews and Focus Group Discussions (FGDs) were conducted for qualitative study to find out their experiences regarding barriers, coping strategies and their needs and expectation when accessing health care services. Physical (spinal cord injury) disability accounted 46.67% while 53.33% were intellectual disabled. 48.3% were in poor health and 51.67% in fair health condition. The total mean values of direct medical cost for both types of disability were Rs. 6682.53 in the past six month. The qualitative reports suggest that people with severe disability faces numbers of barriers in accessing health services. This is seen as the key reason for their poor health outcome. High cost incurred in medical services and physical health maintenance, worse socio-economic status, and layers of barriers in accessing health care services were the reason of poorer health outcome and exclusion from the society. Economic Journal of Development Issues Vol. 23&24 No. 1-2, (2017) Combined Issue, Page : 102-112